Effect of quick-freezing temperature on starch retrogradation and ice crystals properties of steamed oat roll. (November 2020) - Gong, Yuyuan; Xu, Shuya; He, Ting; Dong, Rui; Ren, Tian; Wang, Xiaolong; Hu, Xinzhong
Abstract: Oat roll is one of the traditional oat wholemeal foods. The purpose of this work was to investigate the effects of quick freezing at −20 °C, −40 °C and −80 °C for 90 min before frozen storage on the quality of frozen steamed oat roll. Quick freezing at −40 °C and −80 °C inhibited the increase of peak gelatinization temperature, enthalpy and the ordered degree of oat roll starch, therefore postponing starch retrogradation. The cross-section microstructure confirmed that reducing the quick-freezing temperature could prevent the increase of ice crystals size, ruptured structures and maintain the integrity of internal structure. As the storage time extend, the ice recrystallization led to an increase in size of ice crystals, while a decrease in their number. Frozen steamed oat roll starch had the highest swelling power at the quick-freezing temperature of −80 °C, that indicated strongest water absorption and binding ability when gelatinized again. Texture analysis demonstrated that hardness increased during frozen storage, quick freezing at −80 °C had the best texture properties. Therefore, declining the quick-freezing temperature could obtain a higher quality of frozen steamed oat roll, by means of delaying the starch retrogradation and minimising the size of ice crystals. Graphical abstract: Image 1 Highlights: Retrogradation degree of starch was decreased by quick freezing at −40 °C and −80 °C. Quick-freezing temperature and swelling power had a negative correlation. Damage of ice crystals to microstructure could be reduced by freezing at −80 °C. Declining quick-freezing temperature was conducive to restraining hardness.